The Role of Potential Energy Surface in Quantum Mechanical Tunneling: A Computational Perspective - Reena (My University, 2019)
The work presented here seeks to intensify our understanding of quantum mechanical tunneling (QMT) in hydrogen atom transfer (HAT) reactions. The work focuses on two sorts of the reactions: (i) HAT from different substrate by same radical abstractor and (ii) HAT from same substrate by different radical abstractor. We corroborate QMT in the chemical reactions with an efficient exploration of potential energy surface (PES) using computational approach. The PESs are computed using composite CBS-QB3 method and the obtained energetics are utilized to determine the rate constant for these aforementioned reactions. The rate constants including the effect of tunneling through the barrier have been calculated at three different temperatures 77K, 273K and at 298K. Tunneling corrected KIE values have also been computed using semi-classical Erying’s transition state theory equation and compared with the available experimental findings to ascertain the reliability of the tunneling contribution. It is observed that the probability of tunneling is highly dependent on the symmetry & the narrowness of the PESs. Thereby, this work gives an insight into the importance of tunneling and its contributing factors in simple H-atom transfer reactions.
Keywords: Potential Energy Surface; Quantum Mechanical Tunneling; Reaction rate; Hydrogen atom transfer reactions; Kinetic Isotope Effect